2005
DOI: 10.1093/ecam/neh088
|View full text |Cite|
|
Sign up to set email alerts
|

Complementary and Alternative Medicine in Pakistan: Prospects and Limitations

Abstract: Despite all the marvelous advancements in modern medicine, traditional medicine has always been practiced. More than 70% of the developing world's population still depends on the complementary and alternative systems of medicine (CAM). Cultural beliefs and practices often lead to self-care or home remedies in rural areas and consultation with traditional healers. Evidence-based CAM therapies have shown remarkable success in healing acute as well as chronic diseases. Alternative therapies have been utilized by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
125
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(129 citation statements)
references
References 21 publications
2
125
2
Order By: Relevance
“…Several population-based studies in the developed countries such as in Australia, the UK, Taiwan, Singapore, and the USA reported that one half to two thirds of adults use CAM (Ceylan et al 2009). In developing countries more than 70% of the population still depend on the complementary and alternative systems of medicine (Shaikh and Hatcher 2005). Various scholarly traditional medication systems such as Ayurveda, Amchi, homeopathy, traditional Chinese medicine, Tibetan medicine, shamanistic medicine (faith healing system), and folk medicines exist in Nepal (Gewali 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Several population-based studies in the developed countries such as in Australia, the UK, Taiwan, Singapore, and the USA reported that one half to two thirds of adults use CAM (Ceylan et al 2009). In developing countries more than 70% of the population still depend on the complementary and alternative systems of medicine (Shaikh and Hatcher 2005). Various scholarly traditional medication systems such as Ayurveda, Amchi, homeopathy, traditional Chinese medicine, Tibetan medicine, shamanistic medicine (faith healing system), and folk medicines exist in Nepal (Gewali 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Poor health services offer little for the prevention and treatment of STIs. Various factors, including proximity, affordability, availability, family pressure and strong community opinion, lead to self-care and consultation with traditional healers, hakeems or even quacks 50. Long-held misconceptions continue to contribute to the national neglect of STI treatment and prevention.…”
Section: Discussionmentioning
confidence: 99%
“…A survey held in Singapore in 2005 states that 91% of medical students believe that CAM could play an important role in their future practice (Yeo et al, 2005). The major reason for not including CAM in medical courses can be the lack of education, training, regulation and the evidence base for CAM practioners (Shaikh and Hatcher, 2005).…”
Section: Author(s) Agree That This Article Remain Permanently Open Acmentioning
confidence: 99%